Opportunities and barriers for reimbursement of digital therapeutics in Austria: Findings From expert interviews - Mahdi Sareban; Gunnar Treff; Jan David Smeddinck; Rada Hussein; Josef Niebauer (Digital Health)
Background Digital therapeutics (DTx) are software-based interventions that aim to prevent or treat especially non-communicable diseases. Currently, no framework for reimbursement of DTx exists in Austria. The aim of this study was to gather a comprehensive perspective on regulatory considerations of Austrian stakeholders with regard to reimbursement of DTx and to outline strategies for establishing a national reimbursement framework. Methods Based on a stakeholder analysis, seven semi-structured interviews with Austrian experts from the digital health-related fields medicine, public health, health technology assessment, health industry and social security providers were conducted. Interviews were analyzed according to seven predefined themes. Results Overall, participants agreed that reimbursement of DTx by the public insurance in Austria is desirable. Prerequisites are (i) a high user and prescriber acceptance of DTx, which must be integrated into a transparent and interoperable Austrian e-Health infrastructure, (ii) a sufficient, risk-based level of evidence for clinical effectiveness, (iii) national authorities that transparently provide evidence-base, indications, contra-indications and potential risks, (iv) adopting European regulations about data security, secondary use of data and use of artificial intelligence and (v) a health-economical evaluation of DTx. Conclusion A comprehensive national strategy for reimbursing DTx will need to consider technical, scientific and socio-economical requirements, patient safety and liability, secure health data handling and use of artificial intelligence in order to establish a sound framework with equitable access also for socioeconomically disadvantaged persons in order to address the growing burden of non-communicable diseases.